Avaliação in vitro da atividade anti-Leishmania de compostos sintéticos derivados tiossemicarbazônicos-acridínicos sobre Leishmania infantum - Neves, Pâmela Gabriella Rodrigues das (2021)
Leishmaniasis is a major public health problem, affecting thousands of people annually. The treatment of this neglected disease has several limitations, the drugs used for the treatment of patients have high toxicity, severe adverse effects, difficult administration, and high cost. Being the therapy of this pathology mainly based on the administration of pentavalent antimonials, which have been used since 1945. All these problems result in discontinuation of treatment by patients and, consequently, the emergence of resistant strains. Because of all these treatment difficulties and the absence of vaccines, there is urgency in the search for new therapeutic drugs that are effective against parasites and do not present harm to the patient. Therefore, in this work, we evaluated the anti-Leishmania activity of derivatives acridine-thiosemicarbazone and the reference drug amphotericin B against promastigote and amastigote forms of Leishmania infantum and its cytotoxicity against human erythrocytes. The results showed that the acridine-thiosemicarbazone derivatives (GLDL 03 and GLDL 06) and the reference drug showed activity against promastigotes of L. infantum, with CI50 of 3.512μg/mL, 5.279 μg/mL and 0.955 μg/mL, respectively. The compounds GLDL 03 and GLDL 06 and the amphotericin B were also active against the axênic amastigote forms of L. infantum, with values of CE50 6.201 μg/mL, 7.550μg/mL, 0.476 μg/mL, in this sequence. It was noted these compounds have shown promise in vitro, it is necessary to conduct more detailed studies that identify their mechanisms of action and they can be used in the treatment of leishmaniasis. Owing to these compounds have shown promise in vitro, it is necessary to conduct more detailed studies that identify their mechanisms of action and they can be used in the treatment of leishmaniasis. Thus, the continuity of tests that elucidate such paths is extremely important in the research of a disease so neglected.